2018
DOI: 10.22161/ijeab/3.6.41
|View full text |Cite
|
Sign up to set email alerts
|

Rural Dwellers’ Involvement in Livestock Farming in Egbeda Local Government Area of Oyo State

Abstract: This study investigated the involvement in livestock farming as a mean of livelihood among rural dwellers in Egbeda Local Government Area o f Oyo State, Nigeria. Purposive sampling technique was employed to sample 120 rural dwellers while 120 questionnaires were administered and retrieved. The data collected were subjected to descriptive (percentage, mean, mode, std deviation) and inferential (chi-square and correlation) statistics. The result revealed that majority (63.3%) of the respondent were involved in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…This is possibly because feed constitutes the most expensive aspect of poultry production. This is in line with earlier reports (Okeke et al, 2018, Oyelami andAjanaku, 2019) that finance is one of the major constraints of livestock farmers in the rural area. The result shows that the majority (82.8%) of the respondents strongly agrees that poultry serves as source of income, 76.3% strongly agrees it is a source of meat, 62.4% strongly agrees that poultry is a source of food, 48.4% strongly agrees that poultry is a source of employment, Not fewer than 97.8% of the respondents agrees that they derived job satisfaction in poultry farming.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This is possibly because feed constitutes the most expensive aspect of poultry production. This is in line with earlier reports (Okeke et al, 2018, Oyelami andAjanaku, 2019) that finance is one of the major constraints of livestock farmers in the rural area. The result shows that the majority (82.8%) of the respondents strongly agrees that poultry serves as source of income, 76.3% strongly agrees it is a source of meat, 62.4% strongly agrees that poultry is a source of food, 48.4% strongly agrees that poultry is a source of employment, Not fewer than 97.8% of the respondents agrees that they derived job satisfaction in poultry farming.…”
Section: Resultssupporting
confidence: 93%
“…This shows that respondents involve in the poultry farming in the study area are in their active ages when the strength as well as energy to work is readily available. This corroborates the findings of past studies (Adisa and Akinkunmi, 2012;Gingras et al, 2008, Okeke et al, 2018Oyelami and Ajanaku 2019) who reported that younger people are more involved in livestock farming than aged people. This implies that the younger the farmers the better the productivity.…”
Section: Resultssupporting
confidence: 92%